The Influence Of Leadership Style And Work Discipline On The Performance Off The Employees Of The Quality Assurance Department At Pt Xx - Puspitasari, Ike; Surahman, Guruh Mandala Putra; Elisa, Melinda Nur; Melani, Rima; Putri, Ratna Komala (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine: (1). Leadership influence on the performance of the employees of the quality assurance department at PT XX; (2). The effect of work discipline on the performance of employees of the quality assurance department at PT XX; (3). The simultaneous influence of leadership and work discipline on the performance of employees of the quality assurance department at PT XX. This research method is quantitative research because it uses data in the form of numbers and data analysis. Data obtained through the distribution of questionnaires and performed using IBM SPSS version 23. The population is all employees of the quality assurance department which numbered 125 employees with a sample of 100 employees using probability sampling techniques. Hypothesis testing uses t test (partial) and F test (simultaneous). T-test results (partial) indicate that leadership has a negative effect on employee performance, work discipline has a positive and significant effect on employee performance and the F (simultaneous) test results indicate that leadership and work discipline together affect employee performance.